Expression of differential genes involved in the maintenance of water balance in human skin by Piptadenia colubrina extract - Del Carmen Velazquez Pereda, Maria; de Campos Dieamant, Gustavo; Eberlin, Samara; Werka, Rejane Maria; Colombi, Débora [UNESP]; de Souza Queiroz, Mary Luci; Di Stasi, Luiz Claudio [UNESP] (Wiley, 2010)
Background: Hydration and integrity of the stratum corneum (SC) is an important determinant of skin appearance, metabolism, mechanical properties, and barrier function. The presence of aquaglyceroporins and envelope proteins are crucial to provide greater corneocyte cohesion to keep water and other moisturizers in the skin. Aims: In this study, we evaluated the ability of Piptadenia colubrina, a plant native of South American rain forests, in the expression of genes involved in skin capacitance and SC integrity. Methods: The expression of genes for aquaporin-3 (AQP3), loricrin, involucrin (INV), and filaggrin (FLG) was measured by real-time PCR, using an in vitro model of human keratinocytes incubated with concentrations of 2.5, 5, 10, and 20 mg/mL of a hydroglycolic extract of P. colubrina (HEPC). The amount of AQP3 protein was also tested by immunohistochemistry in human skin explants. Clinical trials were conducted to evaluate the effects of a gel-cream containing HEPC on the glycerol index and skin capacitance. Results: Hydroglycolic extract of P. colubrina increased both the expression and immunoreactivity of AQP3 in cultured keratinocytes and human skin explants. The gene induction to envelope proteins FLG and INV was also observed after cell incubation with HEPC. Skin capacitance was significantly improved in human volunteers under treatment with HEPC-containing cream. Conclusions: The extract of P. colubrina promotes cellular hydration and induces gene expression of envelope proteins providing greater corneocyte cohesion to keep water and other moisturizers in the skin and an appropriate epidermal adhesion. The in vitro findings were clinically confirmed and encourage the clinical use of this compound in skin care products. © 2010 Wiley Periodicals, Inc.
Keywords: Aquaporin-3; Cornified envelope; Filaggrin; Glycerol; Involucrin; Piptadenia colubrina